2023
DOI: 10.1246/cl.230246
|View full text |Cite
|
Sign up to set email alerts
|

Reforming of Ethanol with Carbon Dioxide Catalysed by Gold-promoted Copper-ceria-zirconia Composites

Naoya Inoue,
Yuuki Hatooka,
Shiori Shimidzu
et al.

Abstract: In ethanol CO2 reforming, the addition of Au to 10Cu45Ce45Zr catalyst increased the conversion of ethanol and the yields of H2 and CO which were maximized for 2Au8Cu45Ce45Zr catalyst. TG-DTA measurement of used catalysts suggested that Cu metal species on the active catalysts would be difficult to oxidize, promote the transfer of oxygen to carbonaceous species forming CO and lead to the decrease in coke formation with addition of Au.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In our previous study, Au-promoted Cu catalysts exhibited a similar TG prole where Cu species on catalysts with Au was difficult to be oxidized. 1 TEM measurement was performed for fresh and used 2Ag8Cu67.5Ce22.5Zr catalysts (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous study, Au-promoted Cu catalysts exhibited a similar TG prole where Cu species on catalysts with Au was difficult to be oxidized. 1 TEM measurement was performed for fresh and used 2Ag8Cu67.5Ce22.5Zr catalysts (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…49,50 In a recent study, the CeO 2 -ZrO 2 composite prepared by the sol-gel method was used as a support of Cu metal species in DRE. 1 It was found that CuCeO 2 -ZrO 2 , which was prepared using a zirconium alkoxide, a lump of CeO 2 and copper nitrate, exhibited selective formation of CO and H 2 and showed that the formation of hydrocarbon fragments of C1, C2 and C4 could effectively be inhibited. Furthermore, the addition of Au remarkably enhanced the conversion of ethanol and the yields of CO and H 2 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations